I-mode pedestal relaxation events at ASDEX Upgrade. (14th October 2020) - Silvagni, D.; Eich, T.; Happel, T.; Harrer, G.F.; Griener, M.; Dunne, M.; Cavedon, M.; Faitsch, M.; Gil, L.; Nille, D.; Tal, B.; Fischer, R.; et al.
Abstract: The I-mode confinement regime can feature small edge temperature drops that can lead to an increase in the energy deposited onto the divertor targets. In this work, we show that these events are associated with a relaxation of both electron temperature and density edge profiles, with the largest drop found at the pedestal top position. The relative energy loss is about 1 %, and is thus lower than that of type-I ELMs for the same pedestal top collisionality. Stability analysis of edge profiles reveals that the operational points are far from the ideal peeling-ballooning boundary. Also, we show that these events appear close to the H-mode transition in the typical I-mode operational space in ASDEX Upgrade, and that no further enhancement of energy confinement is found when they occur. Moreover, scrape-off layer transport during these events is found to be very similar to type-I ELMs, with regard to timescales (≍ 800 µs), filament propagation, toroidally asymmetric energy effluxes at the midplane and asymmetry between inner and outer divertor deposited energy. In particular, the latter reveals that more energy reaches the outer divertor target. Lastly, first measurements of the divertor peak energy fluence are reported, and projections to ARC—a reactor that could potentially operate in I-mode—are drawn.